LOS DESAFÍOS CONFRONTADOS POR LOS PROYECTOS CONVENCIONALES DE TRANSPORTE Y EL POTENCIAL DE LOS SISTEMAS INTELIGENTES DE TRANSPORTE PARA UNA CIUDAD EN DESARROLLO, LIMA, PERÚ - Martínez, Manuel J (2019)
This paper presents the challenges to the implementation of conventional transportation projects in developing cities with motorization process and recommends research in Intelligent Transportation Systems.